2010
DOI: 10.1007/s00435-010-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Sperm ultrastructure of three Syllinae (Annelida, Phyllodocida) species with considerations on syllid phylogeny and Syllis vittata reproductive biology

Abstract: Phylogeny of Syllidae is under debate due to new studies based on molecular and morphological data. The noticeable taxonomic diversity of syllids (about 700 listed species) is also mirrored in the array of reproductive strategies as well as in sperm morphology, counting a display of forms already supposed to reflect phylogenetic relationships between the species. The sperm ultrastructure of Syllis gerlachi, S. prolifera and S. vittata is herein presented and compared to the Syllinae species studied previously.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the case of male individuals, hybridizations of all three genes resulted in an overlapping symmetrical staining pattern inside the mesoderm at both sides of the gut, both in the stolon (when present) and in a large number of segments at the posterior part of the stock (Figures 4-6). In most studied syllids gametogenesis starts in segmental ventro-lateral paired gonads, which then shrink and release all gametes to the coelomic cavity, where they become completely mature (Giangrande et al, 2002;Gidholm, 1965;Heacox & Schroeder, 1981a, 1981bLepore et al, 2006;Malaquin, 1893;Musco et al, 2010;Schroeder & Hermans, 1975;Wissocq, 1970). Therefore, this observed expression pattern is likely showing cells related to spermatogenesis, either in the gonads, or already freely floating (and completely filling) in the coelomic cavity, the latter being the most likely explanation of the lack of clearly defined boundaries in the expression pattern revealed by most of the stainings.…”
Section: Expression Patterns Of Vasa Piwi and Nanos During Gametomentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of male individuals, hybridizations of all three genes resulted in an overlapping symmetrical staining pattern inside the mesoderm at both sides of the gut, both in the stolon (when present) and in a large number of segments at the posterior part of the stock (Figures 4-6). In most studied syllids gametogenesis starts in segmental ventro-lateral paired gonads, which then shrink and release all gametes to the coelomic cavity, where they become completely mature (Giangrande et al, 2002;Gidholm, 1965;Heacox & Schroeder, 1981a, 1981bLepore et al, 2006;Malaquin, 1893;Musco et al, 2010;Schroeder & Hermans, 1975;Wissocq, 1970). Therefore, this observed expression pattern is likely showing cells related to spermatogenesis, either in the gonads, or already freely floating (and completely filling) in the coelomic cavity, the latter being the most likely explanation of the lack of clearly defined boundaries in the expression pattern revealed by most of the stainings.…”
Section: Expression Patterns Of Vasa Piwi and Nanos During Gametomentioning
confidence: 99%
“…Interestingly, syllids are known to have an hormonal regulatory system of sex determination which involves the prostomium and the proventricle (Durchon, 1972;Franke, 1983Franke, , 1986bPfannenstiel, 1978;Weidhase et al, 2016;Wissocq & Wolff, 1966). Moreover, they can present successive (Durchon, 1951;Franke, 1986a;Wissocq, 1963) or even simultaneous hermaphroditism (Musco et al, 2010), and it has been shown that proventricle removal induces the formation of male stolons, indicating that additional mechanisms are necessary for female specification (Durchon, 1951;Heacox & Schroeder, 1982;Weidhase et al, 2016). Therefore, the differences between males and females in the expression patterns of Ta-nanos ( Figure 4) and Ta-vasa ( Figure 6) could also be related to the hormonal regulation of sex determination.…”
Section: Expression Patterns Of Vasa Piwi and Nanos During Gametomentioning
confidence: 99%
“…In particular, as observed in other polychaetes such as Sabellidae and Syllidae (Patti et al 2003;Musco et al 2008Musco et al , 2010, the structure of the acrosome can be useful to phylogenetic analysis within the clade.…”
Section: Introductionmentioning
confidence: 99%